Pengaruh Nasionalisme Dan Pengetahuan Perpajakan Terhadap Kepatuhan Wajib Pajak Dengan Kesadaran Wajib Pajak Sebagai Variabel Intervening - Michelle, Gavrilla; Kristanto, Septian Bayu (Asosiasi Dosen Akuntansi Indonesia, 2023)
Taxes are the largest source of revenue in the state budget, where awareness and compliance are needed from taxpayers in order to obtain maximum state revenue. But in fact, even though taxpayers are obedient in paying taxes, awareness within taxpayers themselves is still lacking. This research aims to test whether taxpayers awareness and 2 other factors, which are nationalism and tax knowledge, can influence taxpayers compliance. The method used in this research is a quantitative method. The sample in this research were employee class students at universities in DKI Jakarta. Research data will later be obtained through distributing questionnaires with the sampling technique used, is stratified random sampling. The results from this research showed that: (1) nationalism has a significant and positive effect on taxpayers compliance, (2) tax knowledge has a significant and positive effect on taxpayers compliance, (3) taxpayers awareness has an insignificant and positive effect on taxpayers compliance, (4) nationalism has an insignificant and positive effect on taxpayers awareness, (5) tax knowledge has a significant and positive effect on taxpayers awareness.